Разработка алмазных коронок с гребенчатой формой рабочего торца для бурения направленных скважин - Ососов, И.А.; Будюков, Ю.Е.; Власюк, В.И.; Спирин, В.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The results scientific research and experiment construction works on creation diamond bits for the directed drilling of hole are described. Is shown, that performance diamond bits with the edge form of a working end face and arrangement of tops of crests on curve of equilibrium deterioration, causes a high level of mechanical speed of drilling, increase wear mechanism diamond bearing of a matrix and decrease of intensity of a curvature of hole. The results of industrial tests new diamond bits for drilling the hole are given.